Anatomy and Sonographic Examination for Lateral Epicondylitis: EURO-MUSCULUS/USPRM Approach - Ricci, Vincenzo; Cocco, Giulio; Mezian, Kamal; Chang, Ke-Vin; Naňka, Ondřej; Tamborrini, Giorgio; Kara, Murat; Özçakar, Levent (American journal of physical medicine & rehabilitation, 2023)
OBJECTIVE: The aim of the study is to define a standardized comprehensive sonographic approach for evaluating the different histoanatomical compartments of the lateral elbow. DESIGN: Using high-frequency ultrasound probes, we tried to match the anatomical features of the lateral elbow and its different sonographic patterns in patients with the diagnosis of lateral epicondylitis. Moreover, high-sensitive color/power Doppler assessments have also been performed to evaluate the microcirculation. RESULTS: Modern ultrasound equipment seems to provide an extremely detailed sonographic assessment of the different anatomical layers located in the lateral compartment of the elbow. Moreover, high-sensitive color/power Doppler imaging allows for clear visualization of the perfusion patterns in pathological conditions. CONCLUSIONS: In clinical practice, high-frequency B-mode and high-sensitive color/power Doppler imaging can be integrated with the clinical findings to better define the pain generator(s) for optimizing the management of patients with lateral epicondylitis.
Keywords: Ultrasonography; Tennis Elbow; Elbow; ultrasonografie; Elbow Joint; Humans; loketní kloub; Muscles; tenisový loket; svaly; lidé; loket